Partial Verification Bias Correction In Diagnostic Accuracy Studies Using Propensity Score-Based Methods - Wan Mansor, Wan Nor Arifin (2023)
This research objective was to design PS-based methods with weighted regression and resampling approaches to improve and extend PVB correction under MAR and MNAR assumptions. Three MAR PS-based methods of PVB correction were proposed: 1) Inverse probability weighted logistic regression (IPWLogReg), 2) Scaled inverse probability weighted resampling (SIPW-Resamp) and 3) Scaled inverse probability weighted balanced resampling (SIPW-BalResamp).